Saurida lessepsianus a new species of lizardfish (Pisces: Synodontidae) from the Red Sea and Mediterranean Sea, with a key to Saurida species in the Red Sea - Russell, Barry C.; Golani, Daniel; Tikochinski, Yaron (Zootaxa, 2015)
Saurida lessepsianus n. sp., a lizardfish (Aulopiformes: Synodontidae) from the Red Sea and Mediterranean Sea, previously misidentified as S. undosquamis (Richardson) and more recently as S. macrolepis Tanaka, is described as a new species. It is characterised by the following combination of characters: dorsal fin with 11–12 rays; pectoral fins with 13–15 rays; lateral-line scales 47–51; transverse scale rows above lateral line 4½, below lateral line 5½; pectoral fins moderately long (extending to between just before or just beyond a line from origin of pelvic fins to origin of dorsal fin); 2 rows of teeth on outer palatines; 0–2 teeth on vomer; tongue with 3–6 rows of teeth posteriorly; caudal peduncle slightly compressed (depth a little more than width); upper margin of caudal fin with row of 3–8 (usually 6 or 7) small black spots; stomach pale grey to blackish anteriorly; intestine whitish. The species is common in the Red Sea and as a result of Lessepsian migration through the Suez Canal, it is now widely distributed in the eastern Mediterranean. The taxonomic status of two other Red Sea nominal species, Saurus badimottah Rüppell [= Saurida tumbil (Bloch)] and Saurida sinaitica Dollfus in Gruvel (a nomen nudum), is clarified. A key is provided for the species of Saurida in the Red Sea.